Characteristics of Respiratory Syncytial Virus Infection in Hospitalized Children Before and During the COVID-19 Pandemic in Thailand - Wilawan Chaiut; Ratana Sapbamrer; Sauwaluk Dacha; Tavitiya Sudjaritruk; Ida Parwati; Anton Sumarpo; Rungnapa Malasao (Korean Society for Preventive Medicine, 2023)
Objectives This study compared the epidemiological and clinical manifestations of patients hospitalized with respiratory syncytial virus (RSV) infection before and during the coronavirus disease 2019 (COVID-19) pandemic at a tertiary care hospital in Chiang Mai Province, Thailand. Methods This retrospective observational study utilized data from all cases of laboratory-confirmed RSV infection at Maharaj Nakorn Chiang Mai Hospital from January 2016 to December 2021. Differences in the clinical presentation of RSV infection before (2016 to 2019) and during (2020 to 2021) the COVID-19 pandemic were analyzed and compared. Results In total, 358 patients hospitalized with RSV infections were reported from January 2016 to December 2021. During the COVID-19 pandemic, only 74 cases of hospitalized RSV infection were reported. Compared to pre-pandemic levels, the clinical presentations of RSV infection showed statistically significant decreases in fever on admission (p=0.004), productive cough (p=0.004), sputum (p=0.003), nausea (p=0.03), cyanosis (p=0.004), pallor (p<0.001), diarrhea (p<0.001), and chest pain (p<0.001). Furthermore, vigilant measures to prevent the spread of COVID-19, including lockdowns, also interrupted the RSV season in Thailand from 2020 to 2021. Conclusions The incidence of RSV infection was affected by the COVID-19 pandemic in Chiang Mai Province, Thailand, which also changed the clinical presentation and seasonal pattern of RSV infection in children.